Correlation Between Online Game Addiction and Social Adjustment in Teenage Mobile Legend Players - Insan, Imammul; Sartika , Dewi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to find out whether there is a relationship between online game addiction and social adjustment in teenage mobile legend players. This research uses a quantitative correlation approach with a sampling technique using Accidental Sampling. a total of 176 samples. From the results of data analysis, the correlation coefficient (rxy) was obtained with a positive value, namely 0.473, with a sig value. (p calculated) = 0.0001 or p < 0.05 which shows that the relationship between the two variables is significant. This indicates that young mobile legend players are quite capable of controlling and controlling when playing mobile legend games.